A Human Gonadal Cell Model From Induced Pluripotent Stem Cells - Rodríguez Gutiérrez, Daniel; Eid, Wassim; Biason-Lauber, Anna (Frontiers in Genetics, 2018)
Sertoli cells are main players in the male gonads development and their study may shed light on 46,XY disorders of sex development. Mature primary Sertoli cells are incapable of proliferating in prolonged in vitro cultures and the available Sertoli cell models have several limitations since they derive from mouse or human cancer tissues. We differentiated human fibroblasts-derived induced pluripotent stem cells into Sertoli-like cells and, in order to characterize this new Sertoli cell model, we performed gene expression analyses by new generation sequencing techniques. This approach revealed that our putative Sertoli-like cells have reduced expression of pluripotency markers and expressed Sertoli cell markers such as SRY-Related HMG-Box 9 (SOX9), vimentin (VIM), and claudin-11 (CLDN-11). More in detail, the transcriptional profile analysis suggested that these cells are in an early stage of Sertoli cells maturation. Harnessing the power of induced pluripotent stem cells, we were able to generate Sertoli-like cells that show genetic and functional similarities to human Sertoli cells. Sertoli-like cells could become an excellent source of patient-specific Sertoli cells that could be of paramount benefit for both basic research and personalized medicine in sex development and reproductive medicine.